2005
DOI: 10.2320/matertrans.46.581
|View full text |Cite
|
Sign up to set email alerts
|

Dilatometric Study of Reaustenitisation of High Silicon Bainitic Steels: Decomposition of Retained Austenite

Abstract: The formation of austenite during the heating of high-silicon steels with a microstructure of bainitic ferrite plates separated by carbonenriched regions of retained austenite has been studied. As the steel is heated, retained austenite decomposes into a mixture of ferrite and carbides before a temperature is reached where it becomes the more stable phase and hence can grow. The decomposition makes it necessary for the austenite to nucleate from the mixture of ferrite and carbides. In this work, dilatometric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 21 publications
(18 reference statements)
2
18
0
3
Order By: Relevance
“…The expansion in the dilatometric isothermal holding curve (Fig. 5) should be connected with precipitation of carbides from c phase, which is confirmed by previous findings of other authors [17,22]. During successive cooling, the volume expansion of the sample occurs from the temperature of 416°C (Fig.…”
Section: Determination Of Critical Temperaturessupporting
confidence: 75%
See 3 more Smart Citations
“…The expansion in the dilatometric isothermal holding curve (Fig. 5) should be connected with precipitation of carbides from c phase, which is confirmed by previous findings of other authors [17,22]. During successive cooling, the volume expansion of the sample occurs from the temperature of 416°C (Fig.…”
Section: Determination Of Critical Temperaturessupporting
confidence: 75%
“…They found that decomposition of austenite into the mixture of ferrite and carbides is accompanied by expansion of the specimen, visible on dilatometric curve on heating. In turn, Caballero et al [22] observed that the volume change depends on the content of C in retained austenite. They have stated that contraction of the specimen in 0.8C-2Mn-1.6Si-1.3Cr-0.3Mo steel occurs at carbon concentration above 1.5 %.…”
Section: Determination Of Critical Temperaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, further work is intended to explain in detail the presence of different phases, the effect of strain, composition, and cooling rates. It should be taken into account that plastic deformation shifts diffusion-controlled transformations to a shorter time [31,32]. JMatPro software does not enable the user to take into take into account a grain size after plastic deformation, which is usually successfully decreased during multistep deformation tests [21,24].…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%